Let Me Tell You a Story: History, Political Theory, and Mesoamerica, Part 1 - Christopher Binetti (Polit Journal Scientific Journal of Politics, 2024)
This two-part article attempts to use a novel method- creative non-fiction (or story-telling) to make a serious point about History, Political Theory, and Mesoamerica. Since Mesoamerica is a politically-sensitive topic and because any attempt to apply Political Theory to the history of ancient Mesoamerica may be met with implicit biases, the novel use of creative non-fiction-style story-telling (where all of the facts are portrayed accurately and cited) has been employed before the formal theorization is presented. This combines one of the strengths of traditional Political Theory- the use of the thought experiment with actual historical and archaeological data. The names of places and persons are present not only in the citations throughout the paper but also in the second half of the paper, which analyzes the story and reveals three important themes. This is a natural experiment in which the psychological biases of the reader are tested and allows to compare ancient Mesoamerica to other places, in this case, ancient Italy. This leads to a third theme, that the rise of ancient Mesoamerica through the Mixe-Zoquean civilization (and not the Mayans as many scholars pretend) empirically proves that Aristotle’s theory of the origins of civilization is correct. This paper is in two clear halves to show these three themes from both the theoretical-narrative and historical-empirical perspectives.